Contemporary Review on Technologies and Methods for Converting Unstructured Data to Structured Data - Bolla, Sreenivasulu; Anandan, R (International Journal of Engineering and Technology, 2018)
It is now evident that Big Data has pinched immense contemplation from scientists in data sciences, strategy and chiefs in governments and activities. As the speed of data progress surpasses Moore's Law toward the start of this new century, exorbitant data is making awesome inconveniences to individuals. Be that as it may, there are so much potential and exceedingly helpful esteems covered up in the tremendous volume of data. Be that as it may, huge data significantly contains three classes of data those are organized data, semi organized data, unstructured data. In this paper we are examining the diverse qualities and advancements of Big Data and predominantly concentrating on change of organized data to unstructured data and distinctive innovations required to changing over the data.Â Â